Randomized Controlled Trial Comparing the Effects of 2 Analgesic Drug Protocols in Patients who Received 5 Dental Implants. Issue 3 (June 2017) - Meta, Isaac Fernando; Bermolen, Miriam; Macchi, Ricardo; Aguilar, Jorge
Abstract : Purpose: This randomized controlled trial compares postoperative pain and swelling after placing dental implants in patients treated with nonsteroidal anti-inflammatory drugs (NSAIDs) versus NSAIDs and corticosteroids. Materials and Methods: Thirty patients received 5 dental implants each in the interforaminal region of the mandible. All patients were treated with ketorolac tromethamine 10 mg, 2 tablets daily for 2 days and amoxicillin 500 mg, 3 tablets daily for 7 days starting 24 hours before surgery. Experimental patients received an im injection of betamethasone 2 mL within 10 hours after surgery. Pain perception, intraoral inflammation (InIn), and extraoral inflammation (ExIn) data were collected 3, 7, and 14 days after surgery. Patients filled out a pain visual analog scale. InIn and ExIn were recorded by observing the existence of 7 signs. Results: One patient was excluded from control group. Pain perception, InIn, and ExIn were not different between groups at each time point. However, these variables were different from the previous time point within each group. Conclusion: This study suggests that there is no difference in managing postoperative pain and swelling with betamethasone versus betamethasone and ketorolac.